KARAKTERISTIK FISIKOKIMIA BAKSO DAGING SAPI DENGAN PENAMBAHAN TEPUNG UBI JALAR UNGU (Ipomoea batatas L.) SEBAGAI SUBSTITUSI TEPUNG TAPIOKA (Physicochemical Characteristics of Beef Meatballs with the Addition of Purple Sweet Potato (Ipomoea batatas L.) - Irfansyah, Roni; Wibowo, Ari; Haris, Muh. Ichsan; Anindyasari, Dinar (JURNAL NUKLEUS PETERNAKAN, 2024)
Meatballs are ground beef products that use tapioca flour. This flour can be replaced with purple sweet potato flour (Ipomea Batatas L.) which is rich in antioxidants and nutrients such as vitamins A, C, fiber, iron, potassium and protein. This study aims to determine the effect of adding purple sweet potato flour (Ipomea Batatas L.) as a substitute for tapioca flour on the physicochemical characteristics of beef meatballs. Physical parameters tested included water binding capacity, pH, cooking shrinkage, color, and texture, as well as chemical tests such as protein content. The research was conducted in March and April 2024 at the Faculty of Agriculture, Mulawarman University. This research design uses a complete randomized design (CRD) consisting of 5 treatments and 4 replicates which include: P0 (100% tapioca flour, no purple sweet potato flour), P1 (75% tapioca flour, 25 purple sweet potato flour), P2 (50% tapioca flour, 50% purple sweet potato flour), P3 (25% tapioca flour, 75% purple sweet potato flour), P4 (no tapioca flour, 100% purple sweet potato flour). The results of the analysis of beef meatballs with the addition of purple sweet potato flour as a substitute for tapioca flour had a significant effect (P < 0.05) on pH value, cooking shrinkage, brightness color value (L *), reddish color value (a *), and yellowish color value (b *), but had no significant effect (P>0.05) on water binding capacity, texture, and protein content. The conclusion of this study is that purple sweet potato flour can be a good alternative for tapioca flour substitution in making beef meatballs with additional benefits in the form of improved nutrition and functional properties.